2022
DOI: 10.3121/cmr.2021.1707
|View full text |Cite
|
Sign up to set email alerts
|

ST Segment Elevation Myocardial Infarction in the COVID-19 Era: Appraisal of the Evidence

Abstract: The COVID-19 pandemic continues to present a public health challenge and has had a significant impact on the presentation, time-dependent management, and clinical outcomes of ST elevation myocardial infarction (STEMI). Patients with COVID-19 and pre-disposing cardiovascular risk factors like hypertension, hyperlipidemia, and diabetes mellitus are at a higher risk of developing STEMI, and global trends have highlighted delayed management of STEMI, which may contribute to worse clinical outcomes. Prolonged time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…Also proven from previous study showing that STEMI is associated with HTN, Family history and obesity in young adults specially in males it is found to be prevalent. 11,12,13 American heart association also showed that young adults having Higher blood pressure were more prone to develop Myocardial infarction with higher ST segment elevation. STEMI also found to be associated with obesity and male gender and younger individuals al these results are in accordance with results of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Also proven from previous study showing that STEMI is associated with HTN, Family history and obesity in young adults specially in males it is found to be prevalent. 11,12,13 American heart association also showed that young adults having Higher blood pressure were more prone to develop Myocardial infarction with higher ST segment elevation. STEMI also found to be associated with obesity and male gender and younger individuals al these results are in accordance with results of this study.…”
Section: Discussionmentioning
confidence: 98%